Rethinking justice: unraveling the tapestry of justice in Islamic and western philosophies - Ahmad Munawar Ismail,; Latifah Abdul Majid,; Muhammad Farhan Firas, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Throughout human civilization, justice has been an enduring value, evolving through continuous advocacy. Fueled by human reason, individuals consistently elevate their standards, leading to the transformation of justice derived from natural law, societal changes, and religious doctrines. This dynamic process signifies that humanity, along with its cultures, laws, and justice perceptions, progresses rather than regresses—growing more intricate, sophisticated, and advanced. This article delves into the development of justice concepts in Islamic and Western cultures across classical, modern, postmodern, and contemporary eras. Utilizing a philosophical approach, it argues that justice undergoes a developmental evolution in both cultures—from discussions in the context of natural law to exploring religious justice and culminating in discussions of social justice. Despite epistemological differences, both Islamic and Western cultures remain inseparable from justice principles: enforcing justice, presupposing equality, aligning with truth, embodying equilibrium, and positioning things rightly.